2013
DOI: 10.1007/s11434-012-5621-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of a novel conductance-based technology for environmental bacterial sensing

Abstract: In this study, a simple impedance based technology for measuring bacterial concentrations was developed. The measurement system includes the signal amplification, copper probes and a sample loader. During the experiments, the conductance of Bacillus subtilis var niger, Pseudomonas fluorescens, and Escherichia coli were measured using the combination of a pre-amplifier and a lock-in amplifier. The conductance data were modeled verses the bacterial concentrations. Results indicated that the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
1
6
0
Order By: Relevance
“…Bacteria and fungi are important contributor to both conductance and total organic carbon [16], [55], [56], [57]. In this work, we also observed significant differences in the conductance levels of the melted snow samples and the outdoor air samples (after DI water extraction).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…Bacteria and fungi are important contributor to both conductance and total organic carbon [16], [55], [56], [57]. In this work, we also observed significant differences in the conductance levels of the melted snow samples and the outdoor air samples (after DI water extraction).…”
Section: Resultssupporting
confidence: 68%
“…1, no exact correlation between the conductance and bacterial concentration can be drawn (R 2 <0.1). In our another study, we have shown that the bacterial suspension condutance is an exponential function of bacterial concentration for pure bacterial cultures [57]. In a recent study, it was shown that the conductivity of surface snow varied with seasons, and Ca 2+ was found the key ion in determining the conductivity of the surface [33].…”
Section: Resultsmentioning
confidence: 79%
“…The cell membrane consisting of a lipid bilayer with many proteins is involved in regulating its metabolic activities, where the lipid molecules are oriented with their polar groups [28,36]. There are two major groups of bacterial membrane types: Gram-positive and Gram-negative.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, electrical charges on the particles also play a role in their physical depositions in the lung [20][21][22][23]. Additionally, the charge levels and polarity of the bioaerosols can greatly impact their removal efficiencies and detection by electrostatic means [24][25][26][27][28]. While the level of charges results in different amount of electrostatic force imparted on the aerosols, the charge polarity determines the direction of the electrical force.…”
mentioning
confidence: 99%
“…The conductivity value (σ) of Pseudomonas aeruginosa bacterial cells was determined by referring to the conductivity of Escherichia coli (Gramnegative) bacteria, which was at a concentration of 1 x 10 9 -4 x10 9 cfu/ml; the conductivity was 2 x10 -6 -1.4 x 10 -5 mho/m. Meanwhile, the conductivity value (σ) of Staphylococcus epidermidis refers to the conductivity of Bacillus subtilis (Gram-positive), which was at a concentration of 1x 10 8 -8 x10 8 cfu/ml; the conductivity was 0.5 x 10 -5 -5 x10 -5 mho/m (Fangxia et al, 2013). Pockels coefficient r of the cell membrane was 2.6 pm/V (Hajj et al, 2009), lipid refractive index n e was 1.384, water refractive index n a was 1.342, and the number of pores was given the values as expressed by Martinac et al (2008).…”
Section: Variable Values In Modelingmentioning
confidence: 99%